Construção de um índice para a avaliação do desempenho ambiental de empresas da indústria avícola - Bereta, Vinicius [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Objetivo: Elaborar um índice que possa ser utilizado como suporte às empresas industriais avícolas na avaliação de seu desempenho ambiental relativo à destinação de seus resíduos. Metodologia: Trata-se de um estudo quantitativo, descritivo e de caráter referencial, subdividido em quatro etapas metodológicas, sendo: i) aprofundamento da teoria de avaliação do desempenho ambiental; ii) mapeamento do processo produtivo; iii) identificação dos resíduos gerados no processo; e iv) construção do índice e aplicação em uma empresa como exemplo de utilização. Resultados: Fornecer um diagnóstico para pautar ações visando um melhor aproveitamento dos recursos empregados, tornando a organização mais eficiente em busca da melhoria contínua e um melhor desempenho ambiental. Implicações Gerenciais: Este estudo pretende auxiliar na tomada de decisões gerencias para um melhor desempenho e eficiência ambiental na indústria avícola. Originalidade: Este tema relacionado à indústria avícola ainda é escasso na literatura, mesmo tendo-se em vista a importância econômica deste setor para a economia nacional, a crescente demanda por proteína de origem animal e a necessidade de proteção ao meio ambiente segundo os objetivos de desenvolvimento sustentável presentes na agenda 2030 da Organização das Nações Unidas (ONU).

To develop an index that can be used as support for poultry industrial companies in the evaluation of your environmental performance on the allocation of your waste. Methodology: This is a quantitative, descriptive and referential study, subdivided into four methodological stages, being: (i) deepening environmental performance evaluation theory; ii) mapping of the production process; iii) identification of waste generated in the process; and iv) construction of index and application in a company as an example of use. Results: Provide a diagnosis to guide actions aimed at better use of employees, making the organization more efficient in search of continuous improvement and better environmental performance. Management Implications: This study intends to assist in decision-making manages for better performance and environmental efficiency in the poultry industry. Originality: This theme related to the poultry industry is still scarce in the literature, even with a view to the economic importance of this sector for the national economy, the growing demand for protein of animal origin and the need for protection to the environment according to the objectives of sustainable development in the Agenda 2030 of the United Nations (UN).To develop an index that can be used as support for poultry industrial companies in the evaluation of your environmental performance on the allocation of your waste. Methodology: This is a quantitative, descriptive and referential study, subdivided into four methodological stages, being: (i) deepening environmental performance evaluation theory; ii) mapping of the production process; iii) identification of waste generated in the process; and iv) construction of index and application in a company as an example of use. Results: Provide a diagnosis to guide actions aimed at better use of employees, making the organization more efficient in search of continuous improvement and better environmental performance. Management Implications: This study intends to assist in decision-making manages for better performance and environmental efficiency in the poultry industry. Originality: This theme related to the poultry industry is still scarce in the literature, even with a view to the economic importance of this sector for the national economy, the growing demand for protein of animal origin and the need for protection to the environment according to the objectives of sustainable development in the Agenda 2030 of the United Nations (UN).
Construction of an index to assess the environmental performance of companies in the poultry industry
Keywords: Gestão Ambiental; Resíduos; Indústria avícola; Desenvolvimento sustentável